The governance of religious diversity at the European Court of Human Rights - Koenig, Matthias (International approaches to governing ethnic diversity, 2015)
This chapter explores the role of international courts in the governance of religious diversity. Drawing on recent sociological and socio-legal debates over causes and consequences of ‘judicialization’, the paper explores the impact of the European Court of Human Rights on the accommodation of religious minorities. With institutional autonomy strengthened and litigation rates growing, the Court has since the 1990s moved to greater judicial activism, finding several countries in violation of the right to religious freedom and thus challenging long-established church-state-relations in Eastern as well as in Western Europe. However, there are clear limits to the Court’s support for religious minorities. The Court refrains from full-scale criticism of national religious symbols and its jurisprudence shifts between more or less diversity-friendly versions of ‘secularism’. As a result, not all religious minorities have profited equally from the new legal opportunities provided within the transnational human rights field.